Effect of Seed Treatments on Seed Yield and Quality Parameters in Chickpea Seeds (Cicer arietinum L.) Cv. HC-7 and HC-5 - MS PUNEETH RAJ; VS MOR; AXAY BHUKER (Seed Research, 2025)
The present investigation was carried out at the Department of Seed Science and Technology, CCSHaryana Agricultural University, Hisar, to assess the effect of different biological seed treatments on seed yieldand quality parameters of chickpea (Cicer arietinum L.) cultivars HC-5 and HC-7. The treatments comprised seedinoculation with Rhizobium; seed coating on hydro-primed seeds (6 h at 20 °C) with Bio-NPK combined withdrought-alleviating bacteria (DAB); seed coating with Trichoderma harzianum (2 × 10v CFU g-¹) @ 15 ml kg-¹ seed; and an untreated control. Treated seeds were first evaluated for laboratory seed quality parameters andsubsequently sown under field conditions to study growth, yield, and economic performance. The results revealedthat Rhizobium inoculation significantly improved seed quality and yield attributes in both cultivars, followed byBio-NPK + DAB seed coating, while the untreated control consistently recorded the lowest values. Germinationpercentage was highest in Rhizobium-treated seeds (99.00% in HC-5) compared to the control (93.33% in HC-5).Vigour Index-I was also significantly higher under Rhizobium treatment (2230 in HC-5 and 2600 in HC-7) than inthe control (2071 and 2388, respectively). Field evaluation showed significant effects of treatments on plantheight, number of seeds per plant, seed yield, and benefit–cost ratio. Maximum seed yield was recorded withRhizobium inoculation (28.11 q ha-¹ in HC-5 and 29.78 q ha-¹ in HC-7), whereas the untreated control produced the lowest yields (25.78 and 26.88 q ha-¹, respectively). Post-harvest seed quality analysis further confirmedsignificant improvements in seedling length and Vigour Index-I due to biological seed treatments. The study concludes that Rhizobium inoculation is an effective, economical, and environmentally sustainable seed treatment for enhancing seed quality and productivity in chickpea, with additional benefits from bio-based seed coating treatments such as Bio-NPK + DAB and Trichoderma harzianum.